The reaction between HgBr and O3: kinetic study and atmospheric implications. Issue 20 (16th May 2022) - Gómez Martín, Juan Carlos; Lewis, Thomas R.; Douglas, Kevin M.; Blitz, Mark A.; Saiz-Lopez, Alfonso; Plane, John M. C.
Abstract : We have carried out the first kinetic study of the reaction between HgBr and O3 using the PLP-LIF technique. Our results show that this reaction is the main atmospheric fate of the HgBr radical. Abstract : The rate constants of many reactions currently considered to be important in the atmospheric chemistry of mercury remain to be measured in the laboratory. Here we report the first experimental determination of the rate constant of the gas-phase reaction between the HgBr radical and ozone, for which a value at room temperature of k (HgBr + O3 ) = (7.5 ± 0.6) × 10 −11 cm 3 molecule s −1 (1 σ ) has been obtained. The rate constants of two reduction side reactions were concurrently determined: k (HgBr + O) = (5.3 ± 0.4) × 10 −11 cm 3 molecule s −1 and k (HgBrO + O) = (9.1 ± 0.6) × 10 −11 cm 3 molecule s −1 . The value of k (HgBr + O3 ) is slightly lower than the collision number, confirming the absence of a significant energy barrier. Considering the abundance of ozone in the troposphere, our experimental rate constant supports recent modelling results suggesting that the main atmospheric fate of HgBr is reaction with ozone to form BrHgO.